توليف ، توصيف ، وتطبيق قاعدة شيف ذات أساس حيوي لإزالة المواد العضوية تلويث - عائشة, عشـــــيري; ريان, ناقص; حياة, بريـــــبش; سارة, الاســــود; سمية, غديــــر عمر (Echahid Hama Lakhdar University of Eloued, 2023)
This study aims to utilize and valorize a natural resource in the treatment and purification of contaminated water. A new and recoverable material, modified chitosan/clay (Cs/Cly), was developed for the removal of Congo Red dye (CR) from aqueous solutions. The physical and chemical properties were studied using Fourier-transform infrared spectroscopy (FT-IR) and zero point charge (pHpzc) analysis. The Behnken-Box design was used to investigate the factors affecting the dye removal efficiency, as well as the adsorption process variables (adsorbent dosage, solution pH, temperature, and contact time). The obtained results showed that the highest removal percentage of CR dye (96.731%) could be achieved under optimal adsorption conditions (adsorbent dosage of 0.08g, solution pH of 4, temperature of 60°C, and contact time of 20 minutes). The adsorption results were well described by Pseudo-first-order kinetic model, and the adsorption isotherm followed the Langmuir model with a correlation coefficient (R2=0.88). The thermodynamic study indicated that the process was heat-driven and spontaneous in nature. The maximum adsorption capacity was found to be 165.2 mg/g. These findings confirm that Cs-Benz/Cly. is a superior, recoverable, and environmentally friendly adsorbent material. The outcomes of this research can open avenues for other potential important applications such as real wastewater treatment and removal of heavy metal ions. "الملـخـص تهدف هذه الدراسة إلى إستغلال وتثمين مورد طبيعي في معالجة وتنقية المياه الملوثة حيث تم تطوير قاعدة شيف إنطلاقا من تعديل شيتوزان/طين (Cs/Cly) لتكوين مادة مازة جديدة وقابلة للإسترداد لإزالة صبغة الكونغو الأحمر (CR) في المحاليل المائية. تمت دراسة الخصائص الفيزيائية والكيميائية بإستخدام التحليل الطيفي للأشعة تحت الحمراء لتحويل فورييه (FT-IR) ونقطة الشحنة الصفرية (pHpzc). تم الإستعانة بتصميم (Behnken-Box Design) لتحقيق تأثير العوامل التي تأثر على كفاءة إزالة الصبغة. بالإضافة إلى متغيرات عملية الإمتزاز (الكمية المازة، pH المحلول، درجة الحرارة ووقت الإتصال). أظهرت النتائج التي تم الحصول عليها أن أعلى نسبة إزالة صبغة CR (%96.731)، يمكن تحقيقها تحت ظروف الإمتزاز المثلى )الكمية المازة g0.08، pHالمحلول 4 ، درجة الحرارة °C60 والوقت )20min تم وصف نتائج الإمتزاز بشكل جيد بواسطة النموذج الحركي من الدرجة الأولى الزائفة. وإتبع إيزوتارم الإمتزاز نموذج لانغمير بمعامل الإرتباط R2 =0.88. كما بينت دراسة الديناميك الحرارية أنها طاردة للحرارة وعفوية في الطبيعة. تم العثور على قدرة إمتزاز قصوى بلغت mg/g165.2. تؤكد نتائج هذا البحث أن (Cs-Benz/Cly) هي مادة مازة متفوقة، قابلة للإسترداد و صديقة للبيئة. يمكن لمخرجات هذا البحث أن تفتح نافذة للتطبيقات المهمة الأخرى الممكنة مثل تثبيت مياه الصرف الحقيقية. وإزالة أيونات المعادن الثقيلة . "
Synthesis, Characterization, and application of bioserbent-based Schiff's base for the removal of organic pollutant
مذكرة ماستر هندسة كيميائيةDes thèses génie chimique
Keywords: Schiff base, chitosan, CR dye, adsorption, organic pollutants.; قاعدة شيف، شيتوزان، صبغة CR، الإمتزاز، الملوثات العضوية .